Case Report: Pelvic Actinomycosis - Kateřina Maxová (Prague Medical Report, 2012)
A case of pelvic actinomycosis is presented. The patient is 42-year-old female with a 5 weeks history of pelvic pain. An intrauterine device (IUD) was taken out 3 weeks ago. There is a lump length 9 cm between rectus muscles. Ultrasound, magnetic resonance imaging (MRI) and histology are used to make the diagnosis. Actinomycosis can mimic the tumour disease. The definitive diagnosis requires positive anaerobic culture or histological identification of actinomyces granulas. A long lasting antibiotic therapy is performed.